Do we want legal drugs? - Matyjek, Sebastian (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
Looking for an answer to the question whether we want legal drugs, first we should deepen understanding what a drug is, how it acts what kind of influence on a human being it has? To answer the title question the author has divided the article into four chapters. In the first chapter he defines a drug and points to its origin. In the second chapter the author discusses conditions of drug abuse, presents main definitions and types of addiction. The third chapter describes the current legal status and some attempts to legalize soft drugs. He also describes a problem of marijuana harmfulness. The last chapter presents ways of prevention and models of behaviour to reject temptation of drug use. No matter what kind of drugs: ’soft’ or ‘hard’ we use , each of them leaves a trace and changes to our organism, psychology and human behavior.